2020
DOI: 10.37285/ijpsn.2020.13.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Bio-based Polymer Isolated from Seeds of Buchanania lanzan Spreng with Potential Use as Pharmaceutical Mucoadhesive Excipient

Abstract: This study was aimed to develop an oral bio-based mucoadhesive polymer from seeds mucilage of Buchanania lanzan spreng, belongs to family anacardiaceae. Isolated mucilage was evaluated for mucoadhesive strength and compared with existing polymer. The mucilage showed shear stress results (0.099 ± 0.0001N), with comparable adhesiveness to methocel E5 (0.098 ± 0.0008N). Force of adhesion required to detach the seed mucilage and methocel E5 tablets from the mucin of intestinal tissue were 0.0276 ± 0.0019 (N) and 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Six hours post administration, it was found that the dosage form reached the colonic region. Swelling and distortion in the shape of the tablet were also observed in the colonic region, indicating the drug release in the colon region, and the same observation in similar studies has been observed (Singh et al, 2020(Singh et al, , 2021. The X-ray images in the present study also clearly indicate that the optimized formulation was successfully targeted to the colonic region without any prior drug release.…”
Section: In Vivo Colon Targetingsupporting
confidence: 87%
See 1 more Smart Citation
“…Six hours post administration, it was found that the dosage form reached the colonic region. Swelling and distortion in the shape of the tablet were also observed in the colonic region, indicating the drug release in the colon region, and the same observation in similar studies has been observed (Singh et al, 2020(Singh et al, , 2021. The X-ray images in the present study also clearly indicate that the optimized formulation was successfully targeted to the colonic region without any prior drug release.…”
Section: In Vivo Colon Targetingsupporting
confidence: 87%
“…The current animal study was performed as per the procedure mentioned in the experimental protocol cleared by the Institutional Ethics Committee (001/VPC/IAEC/RESEARCH-2018). New Zealand white rabbits (3-3.5 kg) were selected as the animal models to simulate human colonic environment physiology (Singh et al, 2020, Singh et al, 2021. The rabbits were starved overnight with free access to water.…”
Section: In Vivo Targeting Studymentioning
confidence: 99%
“…The fixed weight (100 mg) of tablets was directly compressed using 6.35 mm flat punches. The compression force was set at 4N for minimizing the effect of physical parameters on drug dissolution. , …”
Section: Tablet Preparationmentioning
confidence: 99%
“…The compression force was set at 4N for minimizing the effect of physical parameters on drug dissolution. 34 , 35 …”
Section: Tablet Preparationmentioning
confidence: 99%